Study on the Regulatory Effect of Water Extract of Artemisia annua L. on Antioxidant Function of Mutton Sheep via the Keap1/Nrf2 Signaling Pathway - Gen Gang; Ruiheng Gao; Ruizhen Li; Xiao Jin; Yuanyuan Xing; Sumei Yan; Yuanqing Xu; Binlin Shi (Antioxidants)
This study was conducted through in vivo and in vitro experiments and aimed to reveal the regulatory effect of water extract of Artemisia annua L. (WEAA) on the antioxidant function of mutton sheep and the underlying mechanism. In the in vivo experiment, 32 Dorper × Han female sheep (3 months old; avg. body weight: 24 ± 0.09 kg) were allocated to four groups (eight lambs/group) and fed a diet containing 0, 500, 1000, and 1500 mg/kg WEAA, respectively. In the in vitro experiments, peripheral blood lymphocytes (PBLs) were cultured with different doses of WEAA (0, 25, 50, 100, 200, 400 µg/mL) to determine the optimal concentration, followed by a 2 × 2 factorial experiment with four treatment groups (six replicates per treatment group): the ML385(−)/WEAA(−) group, the ML385(−)/WEAA(+) group, the ML385(+)/WEAA(−) group, and the ML385(+)/WEAA(+) group. The results showed that WEAA supplementation dose-dependently increased serum, liver and spleen tissue total antioxidant capacity, glutathione peroxidase (GSH-Px), and catalase (CAT) activity while reducing malondialdehyde level (p < 0.05). Moreover, WEAA supplementation significantly upregulated the liver and spleen expression of nuclear factor erythroid 2-related factor 2, superoxide dismutase 2, GSH-Px, CAT and NAD(P)H quinone dehydrogenase 1 (p < 0.05) while significantly downregulating the kelch-like ECH associated protein 1 expression in a dose-dependent manner (p < 0.05), thereby activating the Keap1/Nrf2 pathway with the peak effect observed in the 1000 mg/kg WEAA group. Additionally, supplementation with 100 µg/mL of WEAA had significant antioxidation activity in the culture medium of PBLs. Its action mechanism involved the Keap1/Nrf2 pathway; specifically, WEAA exerted its antioxidant effect by upregulating the gene expression related to the Keap1/Nrf2 pathway. In conclusion, WEAA enhances sheep’s antioxidant capacity by up-regulating Keap1/Nrf2 pathway genes and boosting antioxidant enzyme activity. The results provided experimental support for the potential application of WEAA in intensive mutton sheep farming.